دافعية التعلم وعلاقتها بالتوافق الدراسي لتلاميذ(الحلقة الأخيرة)مرحلة التعليم الأساسي بمحلية شرق النيل بالخرطوم - أحمد, عبد الباقي دفع الله; فضول, محمد صلاح عوض (Journal of Faculty of Education, 2021)
This study aims to investigate the relationship between learning motivation and scholastic adjustment among basic school pupils in East Nile locality. The study also attempts to identify the differences in learning motivation among pupils according to gender, class and pupils' parental educational level. To achieve these aims, the researchers applied the descriptive-correlation method. A Stratified random sample of 570 pupils was selected from different educational sectors in East Nile Locality. Tools of data collection consisted of the following: a preliminary information form, a learning motivation scale in addition to scholastic adjustment scale for basic school pupils. The Statistical Package for Social Sciences (SPSS) has been used to analyze the data by applying the following statistical tests: Pearson correlation coefficient, t-test, Cronbach’s alpha equation and Spearman correlation coefficient. The study arrived at the following results: the pupils’ learning motivation of East-Nile Locality is statistically above the average; there is a significant positive correlation between learning motivation and scholastic adjustment among basic school pupils of East-Nile Locality; there is a positive correlation coefficient between learning motivation and pupils’ fathers’ education;. there is no statistically significant correlation between learning motivation with pupils’ mothers’ educational level; there is no statistically significant difference in learning motivation according to pupils’ class (Seventh-Eight); no statistically significant differences in learning motivation according to pupils’ gender (male-female.mm